Stigma, deforming metaphors and patients' moral experience of multibacillary leprosy in Sobral, Ceará State, Brazil Estigma, metáforas deformadoras e experiência moral de pacientes com hanseníase multibacilar em Sobral, Ceará, Brasil - Marilyn K. Nations; Geison Vasconcelos Lira; Ana Maria Fontenelle Catrib (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
In response to the call for a new Science of Stigma, this anthropological study investigates the moral experience of patients diagnosed with severe multibacillary leprosy. From 2003 to 2006, fieldwork was conducted in the so-called "United-States-of-Sobral", in Ceará State, Northeast Brazil. Sobral is highly endemic for leprosy, despite intensified eradication efforts and a 30% increase in primary care coverage since 1999. Of 329 active leprosy cases at two public clinics, 279 multibacillary patients were identified and six information-rich cases selected for in-depth ethnographic analysis, utilizing illness narratives, key-informant interviews, home visits, participant-observation of clinical consultations and semi-structured interviews with physicians. A "contextualized semantic interpretation" revealed four leprosy metaphors: a repulsive rat's disease, a racist skin rash, a biblical curse and lethal leukemia. Far from value-free pathology, the disease is imbued with moral significance. Patients' multivocalic illness constructions contest physicians' disease discourse. "Skin Spot Day" discriminates more than educates. Patients' "non-compliance" with effective multi-drug therapy is due to demoralizing stigma more than a rejection of care. "Social leprosy" in Northeast Brazil deforms patients' moral reputations and personal dignity. No intuito de criar uma Ciência do Estigma, este estudo antropológico investiga a experiência moral de pacientes diagnosticados com a hanseníase multibacilar. De 2003 a 2006, a pesquisa foi conduzida nos "Estados Unidos do Sobral", Estado do Ceará, Brasil, altamente endêmico para hanseníase apesar da intensificação de erradicação e o aumento de 30% na cobertura de saúde desde 1999. Entre 329 casos de hanseníase, 279 foram identificados como multibacilar e seis casos "ricos em informação" foram selecionados para aprofundamento. Narrativas da enfermidade, entrevistas etnográficas, visitas domiciliares, observação-participante de consultas clínicas e entrevistas semi-estruturadas com médicos foram realizadas. A "interpretação semântica contextualizada" revelou quatro metáforas de "lepra" - uma repulsiva doença de rato, uma infecção de pele com conotações racistas, uma praga bíblica, e uma leucemia letal. Essas metáforas "multivocálicas" contestam o discurso biomédico. A lepra é repleta de significados morais. O "Dia da Mancha" descrimina mais do que educa. A falta de aderência à eficaz poliquimoterapia é causada mais pelo estigma desmoralizante do que pela rejeição ao tratamento em si. A "lepra social" no nordeste brasileiro deforma a reputação moral e a dignidade do paciente.